The Construction of a Digital Agricultural GIS Application Suite - Di Hu; Zongxiang Zhang; Xuejiao Ma; Duo Bian; Yihao Man; Jun Chang; Runxuan Qian (Applied Sciences)
With the increasing expansion and deepening of GIS applications across diverse industries, the limitations of industry-specific GIS application systems in terms of development efficiency, flexibility, and customization have become increasingly apparent. This paper employes the concept of application suites and proposes a design approach for tailored GIS application suites in digital agriculture, considering its specific application requirements. Additionally, it outlines an implementation method based on low-code development and microservice technologies. A GIS application system for digital agriculture was developed to conduct experimental validation. The results indicate that the GIS application suite developed in this study demonstrates readily deployable characteristics, granular assembly capabilities, and ease of scalability, facilitating the rapid development of customized GIS applications for digital agriculture. This approach enhances both development efficiency and flexibility while meeting the customization needs inherent to such applications.